In the factory of “migratory risk”: Latin American women in the French air border regime - Tyszler, Elsa (Frontiers in Human Dynamics, 2025)
Based on field research conducted in 2014 and in 2020–2021 at Paris CDG airport, in the various places that make up the “waiting zone” for foreigners not admitted to the French territory, this article proposes to explore the racialized, gendered and sexualized construction of the “migratory risk” category, and its impact on the people thus classified. Through observations and interviews with people prevented from entering France or continuing their journey to another Schengen state, as well as with police officers working in airport terminals and detention zones, particular targets emerge from the interweaving of power and domination relations structuring the border situation: one of these is the “Latina” woman suspected of coming to work as a prostitute. The study shows that this figure is the result of racist, sexist and classist representations of these women and certainly of the circulation of imaginaries and control practices between the Spanish and French border police in the context of joint operations. Comparing the points of view of the women thus assigned and that of the police officers performing the defence of the French-European air border makes it possible to detect the illegal profiling practices and arbitrary power operated discreetly, on a daily basis, at the airport. This gives rise to systemic violence that is invisible but real, marking the bodies and minds of the women apprehended in this way. In this post-colonial context, women, alone or together, have little room for resistance.